Current recommendations and novel strategies for sustainable management of soybean sudden death syndrome - Rodriguez, Maria Cecilia; Sautua, Francisco José; Scandiani, María Mercedes; Carmona, Marcelo Anibal; Asurmendi, Sebastian (Wiley, 2022)
The increase in food production requires reduction of the damage caused by plant pathogens, minimizing the environmental impact of management practices. Soil-borne pathogens are among the most relevant pathogens that affect soybean crop yield. Soybean sudden death syndrome (SDS), caused by several distinct species of Fusarium, produces significant yield losses in the leading soybean-producing countries in North and South America. Current management strategies for SDS are scarce since there are no highly resistant cultivars and only a few fungicide seed treatments are available. Because of this, innovative approaches for SDS management need to be developed. Here, we summarize recently explored strategies based on plant nutrition, biological control, priming of plant defenses, host-induced gene silencing, and the development of new SDS-resistance cultivars using precision breeding techniques. Finally, sustainable management of SDS should also consider cultural control practices with minimal environmental impact.